INDIGO: a global, randomized, double-blinded, phase 3 study of vorasidenib versus placebo in patients with residual or recurrent grade 2 glioma with an IDH1/2 mutation. - Van den Bent, Martin J.; Blumenthal, Deborah T.; Touat, Mehdi; Peters, Katherine B.; Clarke, Jennifer Leigh; Mendez, Joe Sammy; Welsh, Liam; Mason, Warren P.; Hottinger, Andreas Felix; Sanchez, Juan Manuel Sepulveda; Wick, Wolfgang; Soffietti, Riccardo; et al. (Journal of clinical oncology, 2023)
LBA1 Background: Grade 2 gliomas are slowly progressive, malignant brain tumors with a poor long-term prognosis. Current treatments (surgery followed by observation or adjuvant radiation and chemotherapy) are not curative and can be associated with short- and long-term toxicities. Mutations in isocitrate dehydrogenase (IDH) 1 or 2 occur in approximately 80% and 4% of grade 2 gliomas, respectively, and are a disease defining characteristic in the World Health Organization (WHO) 2021 definition. Vorasidenib (VOR) - an oral, brain-penetrant, dual inhibitor of mutant (m)IDH1/2 enzymes has shown a tolerable safety profile and preliminary clinical activity in phase 1 studies. Methods: In this randomized, double-blind, placebo-controlled phase 3 study (NCT04164901) patients (pts) were randomized 1:1 to receive VOR 40 mg daily or placebo (PBO) daily in 28-day cycles. Patients were stratified by 1p19q status and baseline tumor size. Key eligibility criteria included: age ≥12; KPS >80; residual or recurrent grade 2 IDH1m or IDH2m oligodendroglioma or astrocytoma; measurable non-enhancing disease; no prior treatment for glioma with most recent surgery 1-5 years from randomization; and not in immediate need of chemotherapy/radiation. Primary endpoint: radiographic progression-free survival (PFS) by blinded independent radiology committee (BIRC). Key secondary endpoint: time to next intervention (TTNI). Results: As of 6Sep2022 (2nd planned interim analysis data cutoff), 331 pts were randomized across 10 countries: 168 to VOR and 163 to PBO. Of the 331 pts: median age: 40.4 years (range, 16 to 71); KPS =100: 53.5%; histological subtype: oligodendroglioma: 172 and astrocytoma: 159; median time from last surgery until randomization: 2.4 years. Two hundred twenty-six (68.3%) pts remained on treatment (131VOR; 95PBO). PFS by BIRC was statistically significant in favor of the VOR arm (HR, 0.39; 95% CI, (0.27, 0.56); P=0.000000067). Median PFS: VOR: 27.7 mos; PBO: 11.1 mos. TTNI was statistically significant in favor of the VOR arm (HR, 0.26; 95% CI, (0.15, 0.43); P=0.000000019). Median TTNI: PBO: 17.8 mos; VOR: not reached. All reported P values are one-sided. All-grade adverse events (AEs) occurring in >20% pts receiving VOR vs PBO were alanine aminotransferase increased (38.9% vs 14.7%), COVID-19 (32.9% vs 28.8%), fatigue (32.3% vs 31.9%), aspartate aminotransferase increase (28.7% vs 8.0%), headache (26.9% vs 27.0%), diarrhea (24.6% vs 16.6%), nausea (21.6% vs 22.7%). Common grade ≥3 AEs (>5%): ALT increased (9.6% vs 0%). Conclusions: This is the first prospective, randomized phase 3 study of a targeted therapy in grade 2 mIDH glioma. VOR significantly improved PFS by BIRC compared with PBO with a manageable safety profile. These data demonstrate the clinical benefit of VOR in this pt population for whom chemotherapy and radiotherapy are being delayed. Clinical trial information: NCT04164901.
Gesehen am 02.08.2024